Procesos de contratación de bienes para el cumplimiento de actividades de los proyectos sociales que ejecuta el GADP de Los Ríos en Babahoyo - Roby Argüello, Karen Viviana (2021)
Through the investigation, the processes for contracting goods were analyzed to fulfill the operational activities of the Social Projects Area that are carried out in the Autonomous Decentralized Provincial Government of Los Ríos and in turn identifies deficiencies or problems associated with the acquisition processes. For this purpose, it was determined through the interview and observation applied to the Public Procurement and Contracting Coordinator, Administrative Directorate that the procedures presented for the acquisition of goods have flaws or errors, preventing the procedure from continuing its process. For the effect, a qualitative approach was used under the criteria of the inductive method. In addition, a bibliographic information collection methodology was applied, forming a database where the information of data applied to the institution and other theoretical bases of research carried out at the national level were identified, important parameters for the development of the research, for the analysis of the process of contracting goods, the phases of the contracting process were studied through the current National Public Procurement System It was determined that the guidelines provided by current regulations are not taken into account, thus generating inadequate budgets or, failing that, low budgets, showing that the procedures are not very operational and effective.